Mrs. Harris goes to Paris & Mrs. Harris goes to New York - Gallico, Paul, 1897-1976 (Bloomsbury Publishing, 2022)
Mrs. Harris is a salt-of-the-earth London charlady who cheerfully cleans the houses of the rich. One day, while tidying Lady Dant's wardrobe, she comes across the most beautiful thing she has ever seen in her life--a Dior dress. In all the years of her drab and humble existence, she's never seen anything as magical as the dress before her and she's never wanted anything so badly. Determined to make her dream come true, Mrs. Harris scrimps and saves until one day, after three long, uncomplaining years, she finally has enough money to go to Paris.